Concept analysis in nursing : a new approach - Paley, John, 1948- (Milton Park, Abingdon ; New York, NY : Routledge, 2021)
"Concept analysis is an established genre of inquiry in nursing introduced in the 1970s. Currently, over 100 concept studies are published annually, yet the methods used within this field have rarely been questioned. In Concept Analysis in Nursing: A New Approach, Paley provides a critical analysis of the philosophical assumptions that underpin nursing's concept analysis methods. He argues, provocatively, that there are no such things as concepts, as traditionally conceived. Drawing on Wittgenstein and Construction Grammar, the book first makes a case for dispensing with the traditional concept of a 'concept', and then provides two examples of a new approach, examining the use of 'hope' and 'moral distress'. Casting doubt on the assumption that 'hope' always stands for an 'inner' state of the person, the book shows that the word's function varies with the grammatical construction tit appears in. Similarly, it argues that 'moral distress' is not the name of a mental state, but a normative classification used to bolster a narrative concerning nursing's identity. Concept Analysis in Nursing is a fresh and challenging book written by a philosopher interested in nursing. It will appeal to researchers and postgraduate students in the areas of nursing, health, philosophy and linguistics. It will also interest those familiar with the author's previous book, 'Phenomenology as Qualitative Research"--
OCLC-licensed vendor bibliographic record.
Keywords: Nursing; Concepts; MEDICAL / Nursing / Research & Theory